Faktor -faktor yang Berhubungan dengan Kejadian Hipertensi Pada Lansia di Desa Bukit Kemuning Wilayah Kerja UPT Puskesmas Sukaramai - Mayasari, Endang; Kasumayanti, Erma; Susanti, Awari (Universitas Pahlawan Tuanku Tambusai, 2024)
Hypertension in the elderly is characterized by blood pressure of 160/90 mmHg. Hypertension in the elderly occurs due to lack of physical activity, overnutrition, lack of fruit, vegetable consumption and high sodium consumption. The purpose of the study was to determine the relationship between physical activity, overnutrition, fruit, vegetable and sodium consumption with the incidence of hypertension in the elderly in Bukit Kemuning, Kampar, Riau. The type of quantitative research with a cross-sectional design. with a sample of 50 people using the total sampling technique. Data collection using a 24-hour activity recall questionnaire, microtoise, digital scales, 1x24-hour food recall form, Food Frequency Form (FFQ), and digital tensiometer. Data analysis used univariate and bivariate analysis with chi square. The results of the study obtained 48.1% of respondents with light activity, 37 respondents 71.2% were not overnutrition, respondents had hypertension. There is a relationship between physical activity and the incidence of hypertension in the elderly, there is no relationship between overnutrition (p = 0.181) and the incidence of hypertension in the elderly. Based on this research, it is expected that respondents will routinely carry out physical activities regularly and check their blood pressure at least once a month at the elderly health post.